Evaluation of adrenal tumors and analysis of the metabolic profile of patients with incidentaloma - PEDRO VICTOR GONÇALVES MONTALVÃO; IURI MOURA MANGUEIRA; GABRIEL DA MOTTA ALVES; JOÃO VITOR FAZZIO CORDEIRO; MARCIA HELENA SOARES COSTA; GUILHERME DE ANDRADE GAGHEGGI RAVANINI (Revista do Colégio Brasileiro de Cirurgiões)
ABSTRACT Introduction: Advances in imaging methods have led to an increasingly frequent diagnosis of adrenal gland lesions as incidental findings. Despite progress in this field, there is still limited information regarding the epidemiology of the clinical and metabolic profile of patients with adrenal incidentaloma (AI). The objective is analyze the epidemiology of adrenal tumors at Gaffrée e Guinle University Hospital (HUGG) and compare it with data from the literature. Method: This is a cross-sectional study that included patients of any gender and age who was treated at HUGG for adrenal tumors. Results: The following variables were evaluated: age, gender, functionality, benignity, and size. We also analyzed the metabolic profile of patients with AI, specifically those with mild autonomy cortisol secretion. Out of 31 patients with adrenal tumors, 68% were female. The mean age was 55 years with a standard deviation of ±16.2. 54% of the sample had adrenal incidentalomas. 93.6% of the sample had benign cases. Among the adrenal incidentalomas, 53% were non-functioning. In patients with adrenal tumors, only 10% had metabolic syndrome, while in patients with mild autonomous cortisol secretion, this number rose to 17%. Conclusion: The sample of patients with adrenal tumors and incidentaloma at HUGG presented a prevalence of metabolic complications similar to that found in the literature.